Pulmonary colonisation of patients with cystic fibrosis by Burkholderia cepacia - Butler, Sarah Louise (The University of Edinburgh, 1994)
The spread of Burkholderia cepacia within the cystic fibrosis (CF) population has become a major cause of concern for patients and their carers and represents a significant medical and scientific challenge. B. cepacia was originally believed to be an environmentally ubiquitous organism and of little importance as a human pathogen and therefore our knowledge of the pathogenic potential of this organism is limited. This thesis considers biological properties and potential virulence factors of B. cepacia that may be important in pulmonary colonisation and the immune response in CF patients. The studies have focused on a highly transmissible, epidemic strain of B. cepacia isolated in Edinburgh in 1989 and subsequently responsible for colonisation of CF patients in other regional CF centres.

Prior to this study, environmental B. cepacia in culture collections often comprised strains that may have originated as contaminants from colonised patients. To obtain 'true' environmental strains for comparative studies and to test for the ubiquity of B. cepacia an environmental survey was undertaken. B. cepacia was cultured from a minority of sites and further characterisation of the isolates revealed them to be distinct from CF strains suggesting that environmental strains do not pose a major risk to CF patients.

Representative strains of B. cepacia were investigated for biological properties, in particular expression of cell-associated and extracellular virulence factors. The ability to survive in unfavourable environments, including antiseptics was also examined. The epidemic strain was distinct from the majority of B. cepacia strains in several aspects including the production of melanin, expression of R-LPS and poor motility.

Culture of B. cepacia from the oral cavity and saliva of colonised CF patients suggested that the upper respiratory tract may act as a reservoir, both preceding colonisation of the lower respiratory tract and also contributing to the transmissibility of this strain. Comparative studies of the ability of clinical and environmental isolates of B. cepacia to adhere to buccal epithelial cells and respiratory mucin performed by fluorescent labelling, flow cytometry and ELISA showed that the most pronounced binding was observed with the epidemic strain.

The humoral immune response in CF patients colonised with B. cepacia was investigated by ELISA, incorporating B. cepacia R-LPS, and immunoblotting against LPS, flagella and outer membrane antigens. Elevated levels of specific anti-fi. cepacia IgG, IgA and IgM were observed in serum from CF patients chronically colonised by B. cepacia, especially in those patients colonised by the epidemic strain. The detection of anti-5. cepacia antibodies prior to laboratory isolation of B. cepacia in some patients may aid in the early diagnosis of B. cepacia colonisation. Concentrations of one or more IgG subclasses were raised in CF patients, with substantial individual variation. Following chronic colonisation by B. cepacia, the specific anti-5. cepacia-R-LPS antibody response comprised mainly IgG2 and IgG3. Chemiluminescent opsonophagocytosis assays indicated that CF sera may non-specifically inhibit phagocytosis of B. cepacia.

Resistance of B. cepacia to the bactericidal activity of normal human serum appeared to be determined by the expression of S-LPS, in particular a full O-side chain. The epidemic strain, which expresses R-LPS was serum sensitive; paradoxically, this strain is associated with bacteraemia in CF patients.

The relevance and significance of these results to the understanding of the pathogenesis, transmissibility and management of B. cepacia in CF patients is discussed